Laccase GhLac1 Modulates Broad-Spectrum Biotic Stress Tolerance via Manipulating Phenylpropanoid Pathway and Jasmonic Acid Synthesis. Issue 2 (11th December 2017) - Hu, Qin; Min, Ling; Yang, Xiyan; Jin, Shuangxia; Zhang, Lin; Li, Yaoyao; Ma, Yizan; Qi, Xuewei; Li, Dongqin; Liu, Hongbo; Lindsey, Keith; Zhu, Longfu; et al.
Abstract : Modification of GhLac1 expression leads to redirection of phenylpropanoid metabolism and alteration of JA synthesis to confer broad spectrum resistance to both pathogens and pests. Abstract: Plants are constantly challenged by a multitude of pathogens and pests, which causes massive yield and quality losses annually. A promising approach to reduce such losses is to enhance the immune system of plants through genetic engineering. Previous work has shown that laccases (p-diphenol:dioxygen oxidoreductase, EC 1.10.3.2) function as lignin polymerization enzymes. Here we demonstrate that transgenic manipulation of the expression of the laccase gene GhLac1 in cotton ( Gossypium hirsutum ) can confer an enhanced defense response to both pathogens and pests. Overexpression of GhLac1 leads to increased lignification, associated with increased tolerance to the fungal pathogen Verticillium dahliae and to the insect pests cotton bollworm ( Helicoverpa armigera ) and cotton aphid ( Aphis gosypii ). Suppression of GhLac1 expression leads to a redirection of metabolic flux in the phenylpropanoid pathway, causing the accumulation of JA and secondary metabolites that confer resistance to V. dahliae and cotton bollworm; it also leads to increased susceptibility to cotton aphid. Plant laccases therefore provide a new molecular tool to engineer pest and pathogen resistance in crops.